2013
DOI: 10.1149/05029.0005ecst
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Salens as Catalysts In Electroreductive Cyclization and Electrohydrocyclization: Computational and Experimental Studies

Abstract: The use of chiral Ni(II)-salen derivatives was examined in mediated electrohydrocyclization reactions. Cyclic voltammetry established the existence of a catalytic current. Bulk electrolysis revealed a slight change in the diastereoselectivity of the cyclizations. Computational studies were conducted that showed that Ni(II) and Zn(II) were the best metals for electron transfer, while the analogous Co(II) and Cu(II) compounds would likely not result in effective electron transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Under the anhydrous N 2 -saturated condition, the cyclic voltammograms of NiS-1T, NiS-CC-1T and NiS-CC-2T showed reversible reduction peaks at -1.78 V, -1.72 V and -1.69 V vs. Ag/AgCl QRE, respectively (Figure IV-4a and Table IV-3), corresponding to redox processes of the nickel-salen complexes from Ni(II) to Ni(I) [201][202] . In a similar manner observed for the copper-derivatives, the comparison between the cyclic voltammograms of NiS-1T and those of NiS-CC-1T indicated that the insertion of the carbon-carbon triple bond between the thienyl units and the salen core did not significantly influence a reduction process of both target molecules.…”
Section: Electrochemical Reduction Of Co 2 Of Target Monomersmentioning
confidence: 99%
“…Under the anhydrous N 2 -saturated condition, the cyclic voltammograms of NiS-1T, NiS-CC-1T and NiS-CC-2T showed reversible reduction peaks at -1.78 V, -1.72 V and -1.69 V vs. Ag/AgCl QRE, respectively (Figure IV-4a and Table IV-3), corresponding to redox processes of the nickel-salen complexes from Ni(II) to Ni(I) [201][202] . In a similar manner observed for the copper-derivatives, the comparison between the cyclic voltammograms of NiS-1T and those of NiS-CC-1T indicated that the insertion of the carbon-carbon triple bond between the thienyl units and the salen core did not significantly influence a reduction process of both target molecules.…”
Section: Electrochemical Reduction Of Co 2 Of Target Monomersmentioning
confidence: 99%